French is not so easy to decode: a pilot study - de Chambrier, Anne-Françoise; Atzemian, Myrto; Fayol, Michel; Zesiger, Pascal; Martinet, Catherine (Applied psycholinguistics, 2025)
Although easier to read than English, French has several inconsistent grapheme-to-phoneme correspondences (GPCs) whose impact on decoding performance has been little studied. In the current pilot study, 27 adult participants were asked to read aloud 60 pseudowords containing the ambiguous adjacent letters “an,” “on,” and “in”; the contextual graphemes “g,” “s,” and “e”; and the final consonants “d,” “p,” “s,” and “t”; as well as 60 matched control pseudowords without these characteristics. Results indicated that the grapheme “e” corresponding to /ə/; the final consonants meant to be silent; the grapheme “s” corresponding to /z/; the graphemes “an,” “on,” and “in” corresponding to/ɑ̃/, /ɔ̃/, and /ϵ̃/; and the grapheme “g” corresponding to /ʒ/ gave rise to more unexpected answers than their respective control pseudowords. The unexpected answers seem to be explained by dominant rules partly moderated by the position of the GPC in the pseudowords. These findings highlight that the difficulty of decoding French should not be underestimated and suggest that such GPCs might be the subject of particular educational attention.